Pengaruh Penggunaan Media Powerpoint Terhadap Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMA Negeri 1 Air Putih Kecamatan Air Putih - Dewi, Tri Nanda; Siregar, Chairuddin; Syahlan, Ali (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This research is included in quantitative research. Quantitative research is research that uses numbers either directly taken from research results or data processed using statistical analysis. The research results show that a simple linear regression test uses the IBM SPSS version 27 for Windows tool. The results of calculating the simple regression coefficient above show that the constant coefficient value is 11.184, the independent variable coefficient (X) is 0.738. So we get the regression equation Y = 11.184 + 0.738X. The tcount value is 10,877 with a sig value. 0.001, thus it can be seen that the value of tcount (10.877) > than ttable (1.6626). Likewise, the sig value (0.001) < 0.05. So it can be concluded that Ha is accepted, meaning that there is an influence of the use of PowerPoint media on students' interest in learning in Islamic religious education subjects at SMA Negeri 1 Air Putih, Air Putih District. The Determination Coefficient can be seen from the Adjusted R Square value of 0.582 or 58%. This shows that the variable Use of PowerPoint Media (variable which were not included in this research such as learning strategies, student learning motivation, school environment and so on which were not examined in this research.